2010
DOI: 10.1590/s0066-782x2010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Métodos para identificar o limiar anaeróbio em indivíduos com diabete tipo 2 e em indivíduos não-diabéticos

Abstract: Background: In spite of Anaerobic Threshold (AT) to be widely used on exercise evaluation for different populations, there are few studies comparing methods to identify AT for individuals with type-diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
12
0
4
Order By: Relevance
“…It was observed that RPE scores corresponding to AT in present study were around 12.9 ± 1.8 to 13.6 ± 1.4 for T2D, and 13.7 ± 1.2 to 14.6 ± 1.2 for ND (Table 2). The use of RPE for controlling exercise intensities may be an useful tool to ensure exercise prescription for T2D, once the RPE of 12-14 may help to delimitate the transition of moderate exercise to exercise intensities which eliciting blood glucose to increase [2,8,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that RPE scores corresponding to AT in present study were around 12.9 ± 1.8 to 13.6 ± 1.4 for T2D, and 13.7 ± 1.2 to 14.6 ± 1.2 for ND (Table 2). The use of RPE for controlling exercise intensities may be an useful tool to ensure exercise prescription for T2D, once the RPE of 12-14 may help to delimitate the transition of moderate exercise to exercise intensities which eliciting blood glucose to increase [2,8,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, whenever necessary the second order polynomial function, which consist of applyind the [Lac] workload ratio versus increase workload to identify the vertices and thus confirm the LL intensity (Simões, Moreira, Moffatt, & Campbell, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The lactate threshold (LT) has been applied on aerobic evaluation and exercise prescription for individuals with T2D (Sales et al, 2012;Morais et al, 2011;Motta et al, 2010), once exercise below LT is considered a safe intensity associated to a low metabolic and cardiovascular stress Simões, Moreira, Moffatt, & Campbell, 2010). On the other hand, the benefits of exercise may be dependent of which intensity it is performed (Bahr & Sejersted, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma das principais causas de morte e incapacidade funcional³, está relacionada ao acúmulo de gordura no músculo esquelético, que inibi a sinalização da insulina e diminui a translocação do GLUT-4, principal enzima responsável pela captação da glicose circulante, resultando na hiperglicemia, principal característica da doença 4 . Basicamente os sintomas da diabetes são causados por excesso de glicose no sangue e uma falta de glicose nas células 5 ocorre uma resistência a insulina, levando a diminuição da ação nos tecidos-alvo principalmente fígado, músculos e tecido adiposo 6 .…”
Section: Introductionunclassified